1997
DOI: 10.1074/jbc.272.47.29790
|View full text |Cite
|
Sign up to set email alerts
|

The Beige/Chediak-Higashi Syndrome Gene Encodes a Widely Expressed Cytosolic Protein

Abstract: The human autosomal recessive disorder ChediakHigashi syndrome and its murine homologue beige are associated with the formation of giant lysosomes that cluster near the perinuclear region of cells. We prepared a polyclonal antiserum against a glutathione S-transferase-Beige fusion protein and demonstrated by Western analysis that the beige gene encodes a protein of 400 kDa that is expressed in cultured murine fibroblasts as well as most mouse tissues. The protein was not detected in either cultured fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 19 publications
6
104
1
1
Order By: Relevance
“…We can not distinguish from our data whether the secretory lysosomes are undergoing abnormal fusion, or whether the lysosomal membranes are failing to separate after normal lysosomal fusion events. It was previously shown (20) that lysosomes derived from the beige mouse have the same ability to fuse with other lysosomes in somatic cell fusion systems as WT lysosomes, and that overexpression of the 400 kDa WT CHS protein in beige mouse fibroblasts causes the giant lysosomes to become even smaller and more numerous than those seen in WT cells (21). These results suggested that the 400 kDa protein had no effect on fusion but was inducing fission of lysosomal membranes.…”
Section: Secretory Lysosomes Form Normally In Chs Ctl But Then Fuse Tmentioning
confidence: 92%
See 1 more Smart Citation
“…We can not distinguish from our data whether the secretory lysosomes are undergoing abnormal fusion, or whether the lysosomal membranes are failing to separate after normal lysosomal fusion events. It was previously shown (20) that lysosomes derived from the beige mouse have the same ability to fuse with other lysosomes in somatic cell fusion systems as WT lysosomes, and that overexpression of the 400 kDa WT CHS protein in beige mouse fibroblasts causes the giant lysosomes to become even smaller and more numerous than those seen in WT cells (21). These results suggested that the 400 kDa protein had no effect on fusion but was inducing fission of lysosomal membranes.…”
Section: Secretory Lysosomes Form Normally In Chs Ctl But Then Fuse Tmentioning
confidence: 92%
“…The studies performed to date addressing the function of the defective protein, have produced conflicting results, and roles have been proposed for it in sorting along the endocytic pathway, microtubule transport and lysosome fission (32,21). The unique features of our CTL system have allowed us to investigate the effect of the CHS defect on both the delivery of proteins to lysosomes and the biogenesis of secretory lysosomes in CTL.…”
Section: The Delivery Of Proteins To the Secretory Lysosome Is Normalmentioning
confidence: 99%
“…First, we tested, using immunoblotting, whether the antibody against Beige protein, a mouse homologue of lyst, can react with human lyst. The antibody was raised with the carboxylterminal 89 kDa of the murine Beige protein, which contains the highly conserved BEACH domain and seven WD40 repeats (Perou et al, 1997). This region has 95% identity with human lyst in amino acid sequence (Wang et al, 2000).…”
Section: Green)mentioning
confidence: 99%
“…The membranes were blocked by incubation in TBST (20 mM Tris-HCl buffer pH 8.0, 0.15 M NaCl and 0.1% Tween 20) with 10% skim milk. They were then incubated with affinity purified antibody against lyst (1:500 dilution) (Perou et al, 1997) and the immunoreacting bands were detected using an enhance chemiluminescence (ECL) detection kit (Pharmacia Biotech) or chemiluminescent peroxidase substrate (Sigma, St Louis, MO, USA) (for lyst blotting).…”
Section: Western Blottingmentioning
confidence: 99%
“…8,9 This gene encodes a large cytosolic as well as microtubule associated protein. 4,9,10 The precise function of LYST, however, remains unknown. Mutation analyses of the CHS gene have been somewhat hindered by the large size of the CHS cDNA (13.5 kb), and thus far, only eight pathologic mutations have been identified, all of which leading to a truncated CHS protein.…”
Section: Introductionmentioning
confidence: 99%